2018
DOI: 10.1021/acs.energyfuels.8b02185
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hydrogen and Oxygen Isotopes in Produced Water and Productivity Response of Coalbed Methane Wells in Western Guizhou

Abstract: The characteristics of hydrogen (H) and oxygen (O) isotopes in produced water of coalbed methane (CBM) wells have abundant geochemical indication information. On the basis of the tests of conventional ions and H and O isotopes of 20 water samples produced from CBM wells in western Guizhou, the characteristics of H and O isotopes and productivity response of the wells in the study area have been analyzed in combination with the geological background. The research shows that, if the H and O isotopic compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Generally, a closed groundwater environment is conducive to the enrichment and preservation of CBM while an open groundwater environment is not. Researchers theorize that open hydrological environments are close to oxygenrich water source recharge areas that can enrich Ca 2+ , Mg 2+ , and SO 4 2-, while closed hydrological environments are far from such recharge areas and exhibit Na + , K + , Cl -, and HCO 3 enrichment [22,32,36,37]. With increasing drainage time, the concentrations of K + , Na + , Ca 2+ , Mg 2+ , Cl -, and SO 4 2in the water samples decreased with the gradual discharge of fracturing fluid.…”
Section: Conventional Ion Characteristics and Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, a closed groundwater environment is conducive to the enrichment and preservation of CBM while an open groundwater environment is not. Researchers theorize that open hydrological environments are close to oxygenrich water source recharge areas that can enrich Ca 2+ , Mg 2+ , and SO 4 2-, while closed hydrological environments are far from such recharge areas and exhibit Na + , K + , Cl -, and HCO 3 enrichment [22,32,36,37]. With increasing drainage time, the concentrations of K + , Na + , Ca 2+ , Mg 2+ , Cl -, and SO 4 2in the water samples decreased with the gradual discharge of fracturing fluid.…”
Section: Conventional Ion Characteristics and Productivitymentioning
confidence: 99%
“…When groundwater flows through coal-bearing strata, several hydrogenbearing soluble minerals in the coal seams are dissolved continuously. The lighter H atoms in hydrogen-bearing minerals are easily adsorbed by minerals such as clay, while the heavier D atoms are more likely to undergo an isotope exchange with H atoms in the water, thereby continuously enriching D in the formation water and exhibiting D drift characteristics [22,26]. 18 O is enriched in the surrounding rock.…”
Section: Hydrogen and Oxygen Isotope Characteristics Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [8] found that coalbed-produced waters in the Bide-Santang basin of western Guizhou exhibit a D drift indicative of hydrogen content in the coalbed that is higher than that of oxygen and established a template for identifying water sources. Wu et al [19] analyzed the hydrogen and oxygen isotopes of the water produced by CBM wells. They showed that it was mainly derived from atmospheric precipitation (i.e., meteoric water) and was subject to water-rock interactions and evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CBM co-produced water serves as an indicator of these processes it has been subjected to, which could provide valuable information on its evolution (Moore, 2012). Additionally, CBM co-produced water may act as a signature to allow an improved understanding of CBM preservation and enrichment, which can be used as a tool to analyze gas production rates in the processes of CBM exploration (Wu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%